Low temperature route to prepare LaMnO3 - Daundkar, A.; Kale, Sangeeta N.; Gokhale, Suresh P.; Ravi, V (Materials Letters, 2006)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare LaMnO3(LM) ceramics. Freshly co-precipitated lanthanum and manganese hydroxides gel is allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 300 degrees C to form crystalline LM powders. This is the lowest temperature so far reported for the formation of LaMnO3. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Chemical synthesis; LaMnO3; Precipitation; transmission electron microscopy; X-ray diffraction

Low temperature route to prepare LaFeO3 and LaCoO3 - Jadhav, A. D.; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Materials Letters, 2007)
A combination of digestion and further low temperature calcination to crystallize the product was employed to prepare LaFeO3 (LF) and LaCoO3 (LC) powders. Freshly co-precipitated lanthanum and ferric (or cobalt) hydroxide gels by sodium hydroxide were allowed to react at 100 degrees C under refluxing and stirring conditions for 4-6 h. These oven dried powders were heated at 450 degrees C to from crystalline LF (or LC) powders. The phase contents and lattice parameters were investigated by X-ray diffraction (XRD). Transmission electron microscope (TEM) investigations were carried out to examine the morphology and average particle size of these powders. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; LaFeO3; Precipitation; transmission electron microscopy; X-ray diffraction

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Polypropylene-organoclay nanocomposites containing nucleating agents - Ghugare, S. V.; Govindaiah, P.; Avadhani, C. V. (Polymer Bulletin, 2009)
Polypropylene/organoclay nanocomposites containing nucleating agents, viz., aluminum hydroxybis[2,2-methylenebis(4,6-di-tert-butylphenyl) phosphate (NA21) and 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (Millad 3988), were prepared by direct melt intercalation in a twin-screw extruder. Nucleating agents were added to polypropylene during compounding and their effect on the properties of the nanocomposites was studied. X-ray diffraction (XRD) and transmission electron microscopy (TEM) exhibited clay layers to be intercalated and partially exfoliated. The expansion of inter-gallery distance of the clay layers was governed by the interaction between polypropylene, compatibilizer, and different nucleating agents. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated higher thermal stability and crystallization temperature for nanocomposites compared to virgin polymer. Even a small addition of the nanoscale filler with 0.2% nucleating agents was found to promote concurrently several PP material properties, including improved tensile characteristics, higher Young's modulus, increased thermal stability and rate of crystallization.
Keywords: Nucleating agents; organoclay; Polypropylene nanocomposites; Thermogravimetric analysis; transmission electron microscopy

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Bulk and surface structure characterization of nanoscopic silver doped lanthanum chromites - Desai, P. A.; Joshi, P. N.; Patil, K. R.; Athawale, Anjali A. (Applied Surface Science, 2013)
Crystalline state of lanthanum chromites with silver as a dopant has been studied by X-ray diffraction and transmission electron microscopy reveals microscopic properties of grain boundaries. X-ray photoelectron spectroscopy has been used to analyze surface states with atomic ratio of La, Cr, O and Ag as a dopant. LaCrO3 shows mixed valence states of chromium while the silver doped samples exhibit differences in chromium concentration with the oxidation of Cr3+ to Cr6+ in presence of chromium nitrate as a precursor salt. Trivalent stable state of chromium is observed for samples synthesized by chromic acetate as a precursor salt. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Energy dispersive analysis of X-rays; Microwave combustion synthesis; Perovskite nanostructures; transmission electron microscopy; X-ray diffraction; X-ray photoelectron spectroscopy

Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol - Khan, Shadab Ali; Gambhir, Sanjay; Ahmad, Absar (Beilstein Journal of Nanotechnology, 2014)
As a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in the treatment of cancer. The biosynthesized Gd2O3 nanoparticles were characterized by UV-vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoemission spectroscopy (XPS). The Gd2O3-taxol bioconjugate was confirmed by UV-vis spectroscopy and fluorescence microscopy and was purified by using high performance liquid chromatography (HPLC).
Keywords: bioconjugation; biodistribution; gadolinium oxide; humicola sp; transmission electron microscopy

Biogenic green synthesis of monodispersed gum kondagogu (Cochlospermum gossypium) iron nanocomposite material and its application in germination and growth of mung bean (Vigna radiata) as a plant model - Raju, Dugyala; Mehta, Urmil J.; Beedu, Sashidhar Rao (IET Nanobiotechnology, 2016)
An eco-friendly green and one-pot synthesis of highly monodispersed iron (Fe) nanoparticles (NPs) by using a natural biopolymer, gum kondagogu (GK) as reducing and capping agent is proposed. The NPs synthesised were characterised by ultra-violet-visible spectroscopy, transmission electron microscopy, scanning electron microscopy and X-ray diffraction. As the concentration of gum and time increases, the intensity of NPs formation increased. The NPs were highly monodispersed with uniform circular shapes of 2-6 nm in size. The formed NPs were crystalline in nature which was confirmed by diffraction analysis. The conversion ratio of Fe ionic form to NPs was 21% which was quantified by inductively coupled plasma mass spectroscopy (ICP-MS). Fe is essential for plant growth and development. A study was conducted to examine the effect of these NPs on the growth of mung bean (Vigna radiata). The radical length and biomass was increased in seeds exposed to Fe NPs than the ions. The uptake of Fe NPs by the sprouts was also quantified by ICP-MS, in which Fe was more in mung bean seeds exposed to NPs. The -amylase activity was increased in the seeds exposed to NPs. The observed increase in the biomass by Fe NPs and seed germination may facilitate its application in the agriculture as an important cost-effective method for plant growth.
Keywords: alpha-amylase activity; Biogenic green synthesis; biological techniques; Biomass; Cochlospermum gossypium; diffraction analysis; enzymes; Fe; gum concentration; high-monodispersed iron nanoparticles; inductively coupled plasma mass spectroscopy; ionic-to-nanoparticle iron conversion ratio; iron; monodispersed gum kondagogu; monodispersed gum kondagogu iron nanocomposite material; mung bean germination; mung bean growth; Nanobiotechnology; Nanocomposites; nanoparticle formation; Nanoparticles; natural biopolymer; plant growth; plant model; scanning electron microscopy; size 2 nm to 6 nm; transmission electron microscopy; ultraviolet spectra; ultraviolet-visible spectroscopy; Vigna radiata; visible spectra; X-ray diffraction

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy

Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra